Documentation Of Software Testing For Dafbin Aplication With IEEE 829-2008 Standar - Diyan Febriana Nur Utami; RR Hutanti Setyodewi (Jurnal RESTIKOM : Riset Teknik Informatika dan Komputer, 2023)
PT Qatros Teknologi Nusantara is one of the companies that is an internship partner of Kampus Merdeka. PT Qatros Teknologi Nusantara is a technology startup that offers various services for digital product needs (consulting, development, maintenance) and human resource needs (specific in-house training, public training, bootcamp training). PT Qatros Teknologi Nusantara provides projects to internship students to build a Business Intelligence-based system. Until now, the Dafbin application still does not have testing documentation because the Dafbin application is a newly developed application that will later be released on PlayStore. During this testing process using the IEEE 829-2008 Software Testing standard to provide an evaluation of the features of the software being developed. This documentation work uses the Software Testing Life Cycle (STLC) method where the stages of the testing process are carried out systematically and planned. The final results obtained are documentation in the form of test scenarios based on 4 aspects of the system and attachments to the IEEE-829 standard MTP (Master Test Plan) document